Empowerment of Developed Villages Through Education and Training in Product Diversification of Panada Filling Morning Leaf as An Effort for Stunting Prevention - Yusriani; Alwi, Muhammad Khidri; Rosada, Ida; Handayani, Rika (International Conference on Sustainable Health Promotion, 2023)
Stunting is one of the nutrition problems that is currently the government’s focus. To prevent stunting in children, mothers need to consume proper nutrition and have good nutritional knowledge. The maternal and child health program (KIA), especially the provision of health education in Pucak Village, has not gone well so that 21 cases of stunting were found, 15 pregnant women had anemia and 12 KEK. in pregnant women and toddlers by using local ingredients of Moringa leaves because Moringa leaves have high nutritional value. The method used in this community service activity is health education and local food processing training in preventing stunting. The result of this activity was that there was an increase in the community’s knowledge and skills after being given education and training on stunting and participants were able to red demonstrate processing Moringa leaves in the form of Panada filled with Moringa leaves. The results of community service activities show an increase in the knowledge, attitudes and skills of Cadres and Youth Organizations to utilize local ingredients, namely Moringa leaves as a functional food in preventing stunting in children.